Identification and characterization of the binding sequences and target genes of p53 lacking the 1st transactivation domain - Suzuki, Shiori (Cancer Sci, 2020)
The tumor suppressor gene p53 encodes a transcriptional activator that has two transactivation domains (TAD) located in its amino terminus. These two TAD can transactivate genes independently, and at least one TAD is required for p53 transactivation function. The 1st TAD (a.a. 1‐40) is essential for the induction of numerous classical p53 target genes, while the second TAD (a.a. 41‐61) suffices for tumor suppression, although its precise molecular function remains unclear. In this study, we comprehensively identified the sites to which p53 lacking the 1st TAD (Δ1stTAD‐p53) binds, as well as its potential target genes. We found that the binding sequences for Δ1stTAD‐p53 are divergent and include not only the canonical p53 consensus binding sequences but also sequences similar to those recognized by a number of other known transcription factors. We identified and analyzed the functions of three Δ1stTAD‐p53 target genes, PTP4A1, PLK2 and RPS27L. All three genes were induced by both full‐length p53 and Δ1stTAD‐p53, and were dependent on the transactivation activity of the 2nd TAD. We also found that two of these, PTP4A1 and PLK2, are endoplasmic reticulum (ER) stress‐inducible genes. We found that upon ER stress, PTP4A1 suppresses apoptosis while PLK2 induces apoptosis. These results reveal a novel Δ1stTAD‐p53 downstream pathway that is dependent on the transcription activation activity of the 2nd TAD.